‘Doxorubicin and MBO-asGCS Oligonucleotide Loaded Lipid Nanoparticles Overcome Multidrug Resistance in Adriamycin Resistant Ovarian Cancer Cells (NCI/ADR-RES) - Siddiqui, Akhtar (2012)
The objective of this study was to increase the potency of doxorubicin against adriamycin-resistant NCI/ADR-RES cells by concurrent treatment with doxorubicin and MBO-asGCS loaded solid-lipid nanoparticles (SLN). Loading doxorubicin as ion-pair complex with deoxytaurocholate into cationic and neutral SLN was investigated. Fast release and poor entrapment were observed in cationic nanoparticles, which were corrected by entrapping the complex in neutral polyoxyethylene (20) stearyl ether (Brij(®) 78)/VitE-TPGS nanoparticles. Slow doxorubicin release confirmed the influence of charge and electrolytes on the dissociation of ion-pair complexes. To evaluate antitumor activity, NCI/ADR-RES cells were treated with separate SLN: one loaded with doxorubicin and another carrying MBO-asGCS oligonucleotide. The viability of cells treated with 5μM doxorubicin was reduced to 17.2% whereas viability was reduced to 2.5% for cells treated with both 5μM doxorubicin SLN and 100nM MBO-asGCS SLN. This suggested enhanced apoptosis due to sensitization and effective intracellular delivery of MBO-asGCS and doxorubicin by SLN.